impact de facteur scaling sur les performances du VLC OFDM - دردقه, ياسين; كحلة, عبد المنعم (univ-eloued, 2021)
"Visible light communication (VLC) is a promising system in optical wireless communication . Due to the advantages it offers that are not available in other systems, such as electromagnetic interference that does not exist and its exploitation of the visible spectrum. It is also an alternative to the wireless intercom system. And because VLC requires high data rates, OFDM is capable of transmitting high data rates. DCO-OFDM technology came to link the two systems to reach the highest level of information transfer Therefore, we focused in this research on the study and analysis of the DCO - OFDM system, and also clarifying the effect of facteur scaling on the performance of the system in terms of BER/SNR and PAPR in 4-QAM 16-QAM 64-QAM modulation techniques" "االتصاالت الضوئية المرئية (VLC) هي نظام واعد في االتصاالت الالسلكية الضوئية نظرا لما تقدمه من مميزات ال تتوفر في باقي االنظمة االخرى مثل التداخل الكهرومغناطيسي الغير موجود واستغالله للطيف المرئي .والتي تعتبر بديل لنظام االتصال الالسلكي الداخلي .وألن نظام ال VLC يتطلب معدالت بيانات عالية ، فإن ال OFDM قادر على إرسال معدالت بيانات عالية . وجاءت تقنية DCO-OFDM للربط بين النظامين للوصول الى اعلى مستوى من نقل المعلومات .لذالك ركزنا في هاته المذكرة على دراسة وتحليل نظام DCO - OFDM وايضا توضيح تاثير facteur α على أداء .QAM (4-16-64) تضمين تقنيات في PAPR و BER ا"
Systeme de telecommunication مذكرة ماستر تخصص
Keywords: Visible light communication; االتصاالت الضوئية المرئية